2000
DOI: 10.1128/mcb.20.18.6913-6922.2000
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Delta1, Jagged1, and Jagged2 to Notch2 Rapidly Induces Cleavage, Nuclear Translocation, and Hyperphosphorylation of Notch2

Abstract: Delta1, Jagged1, and Jagged2, commonly designated Delta/Serrate/LAG-2 (DSL) proteins, are known to be ligands for Notch1. However, it has been less understood whether they are ligands for Notch receptors other than Notch1. Meanwhile, ligand-induced cleavage and nuclear translocation of the Notch protein are considered to be fundamental for Notch signaling, yet direct observation of the behavior of the Notch molecule after ligand binding, including cleavage and nuclear translocation, has been lacking. In this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
127
0
4

Year Published

2001
2001
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(135 citation statements)
references
References 65 publications
4
127
0
4
Order By: Relevance
“…Notch1 has Ͼ20 EGF repeats that contain a consensus sequence for O-fucosylation and most may be modified by Fringe (7). It is known that the action of Fringe in transferring GlcNAc to EGF-O-fucose causes changes in soluble ligand binding to Notch receptors (5,(13)(14)(15). We have shown that Lec13 mutant cells with low fucose in glycoproteins exhibit reduced Notch signaling for both Jagged1 and Delta1 ligands (refs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notch1 has Ͼ20 EGF repeats that contain a consensus sequence for O-fucosylation and most may be modified by Fringe (7). It is known that the action of Fringe in transferring GlcNAc to EGF-O-fucose causes changes in soluble ligand binding to Notch receptors (5,(13)(14)(15). We have shown that Lec13 mutant cells with low fucose in glycoproteins exhibit reduced Notch signaling for both Jagged1 and Delta1 ligands (refs.…”
Section: Discussionmentioning
confidence: 99%
“…It is found on urokinase-type plasminogen activator (uPA) (8), on Notch receptors and their ligands (6,9), on Cripto (10,11), and on other proteins, including blood clotting factors. O-Fucose is required for signaling by uPA through the uPA receptor (12), for Fringe modulation of Notch receptor signaling in Drosophila (4,5) and in coculture assays (4,(13)(14)(15)(16), and for Cripto to mediate Nodal signaling (10,11).…”
mentioning
confidence: 99%
“…Post-translational phosphorylation of all Notch proteins was also observed (Fig. 3), N2 and N3 modifications have been previously noted (32,33). Although the Notch ⌬E constructs used in this paper include the analogous S2 cleavage site (Fig.…”
Section: Regulated Intramembranous Proteolysis May Be a Commonmentioning
confidence: 93%
“…Where the specificity in DSL-Notch signaling lies is not well understood. Although it is not known which DSL proteins can activate which Notch molecules, the DSL proteins Jagged1, Jagged2, and Delta1 have been reported to bind Notch2 and subsequently induce processing, indicating that multiple DSL proteins can activate a specific Notch molecule (22). Furthermore, soluble forms of the extracellular domain of Jagged1 can physically interact with Notch1, Notch2, and Notch3 in binding assays (23,24).…”
mentioning
confidence: 99%